New species of ptyctimous mites (Acari, Oribatida) from the Peruvian Andes - Niedbała, Wojciech; Magowski, Wojciech Ł. (Zootaxa, 2024)
New records of ten species (total 109 specimens) of ptyctimous mites collected from a mountain forest in the Peruvian Andes are presented. Five of these species are new for science: Mesotritia andensis Niedbała sp. nov., Austrophthiracarus conchamarcensis Niedbała sp. nov., A. pachiteaensis Niedbała sp. nov., Notophthiracarus churubambensis Niedbała sp. nov. and N. quasipedanos Niedbała sp. nov. Acrotritia ischnos (Niedbała, 2004) is recorded for the first time from Peru; besides, a split into two groups of different body sizes is recorded for a population of Mesotritia curviseta (Hammer, 1961).